Investigation of heat-collecting properties of asphalt pavement as solar collector by a three-dimensional unsteady model. (April 2015) - Li, B.; Wu, S.P.; Xiao, Y.; Pan, P.
<x content-type="archive" xml:space="preserve">Abstract</x> Using asphalt pavement as a solar collector is a technology of increasing interest in China. Researchers have pointed out that the heat quality of the coolant medium needed further investigation for inter-seasonal storage, though the energy potential of an asphalt solar collector was considerable. In this paper, a three-dimensional unsteady model is developed to investigate the heat-collecting properties of asphalt solar collector at typical Chinese summer time. The temperature rise of outlet water (ΔT) is used as the indicator of heat quality. The results from a big-scale slab of 4 m × 4 m show that ΔT reaches over than 10°C, while the asphalt pavement is cooled down effectively. In addition, the higher the ambient temperature is, the better the heat-collecting properties of asphalt solar collector achieves. It can be concluded that the heat-collecting properties of asphalt solar collector are good enough to provide high-quality heat under certain conditions.